Almost Enclosed Buckyball Joints: Synthesis, Complex Formation, and Computational Simulations of Pentypticene‐Extended Tribenzotriquinacene. Issue 17 (18th September 2014) - Henne, Stefan; Bredenkötter, Björn; Alaghemandi, Mohammad; Bureekaew, Sareeya; Schmid, Rochus; Volkmer, Dirk
Abstract We report the synthesis of a tribenzotriquinacene‐based (TBTQ) receptor (3) for C60 fullerene, which is extended by pentiptycene moieties to provide an almost enclosed concave ball bearing. The system serves as a model for a self‐assembling molecular rotor with a flexible and adapting stator. Unexpectedly, nuclear magnetic resonance spectroscopic investigations reveal a surprisingly low complex stability constant of K1=213±37 M−1 for [C60⊂3], seemingly inconsistent with the previously reported TBTQ systems. Molecular dynamics (MD) simulations have been conducted for three different [C60⊂TBTQ] complexes to resolve this. Because of the dominating dispersive interactions, the binding energies increase with the contact area between guest and host, however, only for rigid host structures. By means of free‐energy calculations with an explicit solvent model it can be shown that the novel flexible TBTQ receptor 3 binds weakly because of hampering entropic contributions.